If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-1/2(3n-6)=n+2
We simplify the equation to the form, which is simple to understand
9-1/2(3n-6)=n+2
Simplifying:
9-0.5*(3n-6)=n+2
Reorder the terms in parentheses
9+(-1.5n+3)=n+2
Remove unnecessary parentheses
+9-1.5n+3=+n+2
We move all terms containing n to the left and all other terms to the right.
-1.5n-1n=+2-9-3
We simplify left and right side of the equation.
-2.5n=-10
We divide both sides of the equation by -2.5 to get n.
n=4
| 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 | | 5x+45-3x=15 | | x+(x+5)+x+(x+5)=86 | | 2.25-.25g=.50g | | 5x+45+3x=15 | | 23x^2+22x=0 | | s^2=18-3s | | X+x+5+x+x+5=86 | | 23x+22x=0 | | (8p+4)+(9p+9)= | | 3+x=-8 | | a/5-1/5=-5 | | 1x+2=1x+3 | | 23.0*432*19= | | 9r^2+3r-30=0 | | 12x+2(5-2x)=6 | | -3(x-4)=9x |